Integration of the Maternal Death Prevention Program based on the Health Belief Model Framework (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
In 2015, the Health Office of Banyumas Regency records 7 cases of maternal deaths, 243 cases of infant deaths, and 41 cases of under-five deaths. Compared to 2015, maternal mortality increases in the first three months of 2016. This research aims to identify the causes of maternal deaths that occur in 2016 in Banyumas Regency using the Health Belief Model conceptual framework. The results show that the cause of maternal death in Banyumas Regency is the lack of antenatal services due to the lack of knowledge and awareness of mothers, social status of women in the community, availability of health facilities, vulnerabilities received, benefits of antenatal services, barriers to access to health services, and quality of health facilities and health workers. The problem solving plan is based on the HBM concept framework that can be prepared consisting of stakeholder advocacy, health promotion programs through counseling for pregnant women, programs to improve access to health facilities, and intervention programs for health workers.